Low-wage Jobs: A Means for Employment Integration of the Unemployed? Evidence from Administrative Data in Germany and Austria - Carola Grün; Helmut Mahringer; Thomas Rhein (Austrian Institute of Economic Research (WIFO), 2010)
Does the low wage sector serve as a stepping stone towards integration into better-paid jobs or at least towards integration of jobless people into employment? There is evidence for a "low-wage trap" and for a high risk of low-wage earners to get unemployed, but this may also be due to sorting effects and not to low-wage work itself. The present paper contributes to this debate analysing employment spells of male low-wage earners who had been unemployed before, with methods of continuous-time event history analysis. The present data have been retrieved from two large administrative micro-data sources: the IAB employment sample (IABS) for Germany, and a combination of social security data from the Austrian Social Insurance Institutions. Two possible exits of low-wage spells are focused on: exits to higher-paid employment (upward mobility vs. persistence), and exits to unemployment ("no pay-low pay cycle"). The results show shorter spell durations in Austria, pointing to a considerably higher fluctuation and labour turnover in the Austrian labour market. The influence of individual and firm-related characteristics and of the individual unemployment history on exit probabilities and the role of duration dependence in both countries is investigated. With regard to upward mobility, no convincing evidence for "true" duration dependence is found, at least for Germany. As to the risk of falling back into unemployment, the results suggest that even low-wage workers can accumulate job-related human capital favouring employment integration over time.
Keywords: 330; unemployment dynamics; low wage; duration analysis; Atypische Beschäftigung; Arbeitslosigkeit; Arbeitsmarktintegration; Beschäftigungseffekt; Deutschland; Österreich